What's in it for me? - An analysis of environmental investments through a game theoretic lens. (2016) - Mueller, David
Investments in clean technology are cost-intensive and risky, so cost- and risk-sharing between several firms is a rational option. As each company strives for the largest possible share of gain, the question arises of how the jointly generated benefit should be shared. A mechanism is sought that is judged to be fair and is therefore accepted by the partners. Several solution mechanisms are available if such investments are interpreted as a cooperative game. The nature, characteristics and calculation of these mechanisms are discussed in this paper. Moreover, the most important properties of cooperative games are presented. Different solution concepts will be discussed and their (dis-)advantages are highlighted.